Upaya Penanggulangan Tindak Pidana Aborsi yang Dilakukan oleh Anak di bawah Umur - M. Gibransyah; Dona Raisa Monica; Maroni Maroni (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
This research aims to analyze efforts to overcome the law of abortion killings committed by children on unborn babies. The type of research used is yuridis normative doctrinal. Data sources were obtained from journal and library sources. The results of the analysis show that the crime of abortion murder was committed by a child. In this case, the judge sentenced the child perpetrator to imprisonment for 6 (six) months and 3 (three) months of work training. And whether the judge's decision is in accordance with the objectives of the sentence, what is certain is that in this case there are 3 theories that contain the judge's decision that fulfills the objectives of the sentence, namely the Absolute Theory, the Relative Theory and the Combined Theory.